(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
This article examines the current state of the mortgage lending market in the Russian Federation. An overview of key market indicators over the past ten years is presented. studied modern trends in the development of mortgage lending in the Russian Federation with an emphasis on the dynamics of mortgage rates, analyzed banking programs that offer their borrowers minimum interest rates; studied state support programs, both at the federal and regional levels.